Dzieje Kościoła ormiańskiego w Polsce na tle pasterskiej działalności jego arcybiskupów (rys historyczny) - Koczwara, Stanisław (Vox Patrum, 2002)
This article shows eight centuries of Polish Armenians' history. Peaceful coexistence between the Armenian nation and Polish people, who represented western culture, resulted in the catholic union with the Apostolic See, which appeared to be solid. Armenian archbishops rendered a great service to consolidate the union. Most of the them were great patriots, who merged perfectly Armenian tradition and heritage with Polish culture.